Engaging transformed fundamentals to design global hybrid higher education. Issue 1 (2nd January 2021) - Coates, Hamish; Xie, Zheping; Hong, Xi
ABSTRACT: The year 2020 began with grand ideas about building future higher education. Thereafter universities have been through a constant swirl of uncertainties and confusions as they respond to a novel suite of radically reconfigured fundamentals and prospects. This essay charts this journey in order to document 2020 experiences and to clarify evolving circumstances. We present our personal situations as the basis for articulating perspectives. We discuss shifts with higher education systems, education reconfigurations, research developments, the mobility of students, and faculty members. Finally, we explore the need and opportunity to design future higher education. Engaging with transformed fundamentals provides a means, we propose, to design a new, global hybrid higher education.